Meu dinheiro tem cor” Afroempreendedorismo brasileiro e identidade - Nascimento, Eliane Quintiliano (2020)
The historical, social and economic elements are presented to demonstrate what, supposedly, drives the entrepreneurship of the black population in Brazil, which represents a majority in the country. Of the total Brazilian entrepreneurs, 51% declared thems